The Effect Of A Suggested Training Program On The Levels Of Bodily-kinesthetic Intelligence Of Football Beginners Less Than 15 Years - Guettaoui , Mahfoudh; Boumasjed, Abd Elkader (sports creativity, 2025)
This study aimed to test a training program effect on the levels of bodily-kinesthetic intelligence among soccer beginners category less than 15 years, The researcher used the experimental method in the only group way , the research community of (25) players registered at 2018/2019 sport season, 20 players were selected in The intended way , the exploratory study was conducted on (05) players, while field study was conducted on 15 players ,To measure the bodily-kinesthetic intelligence the researcher built five tests measuring five dimensions of bodily-kinesthetic intelligence: (Body control, sensitivity of rhythm , Expressiveness , Generation of movement ideas , Object manipulation) , The researcher used (SPSS ) program to process data statistically , The results showed a complete improvement in bodily-kinesthetic intelligence